HEPARIN-INDUCED THROMBOCYTOPENIA IN PATIENT POST LIVER TRANSPLANTATION - M. Sh. Hubutija; S. V. Zhuravel’; N. K. Kuznetsova; Е. V. Klychnikova; L. V. Donova (Вестник трансплантологии и искусственных органов)
The widespread use of heparin as an anticoagulant has led to the formation of the problem of heparin-induced thrombocytopenia (HIT). At the present time, the number of different areas of surgical practice, in which we have to face this threat complication, is increasing. We present the clinical case of HIT in a young patient after liver transplantation. Diagnostics of HIT allowed in time to establish the cause of massive thrombus formation, perform liver transplantation, exclude the use of heparin and save the life of the patient.